2017
DOI: 10.11637/kjpa.2017.30.1.7
|View full text |Cite
|
Sign up to set email alerts
|

The Morphometric Study of Main Bronchus in Korean Cadaver

Abstract: : This morphometric study of main bronchus was performed to provide the basic data necessary for anatomists, anesthetists and emergency medical technicians. A total of 48 cadavers, 33 men and 15 women, were used in this study. When it comes to their average age, men were 70 years old (50 to 91 years old), and women were 74 years old (47 to 92 years old). For this study, the length of the left and right main bronchi and the angle between them, and the first bronchial cartilage's each anteroposterior diameter, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In studies conducted on adults, the lengths of the main bronchus were found to be greater in males than in females [7,18,20,24,27,36]. In studies examining the lengths of the right and left main bronchus in children [18,25] and adults [18,20,21,24,27,37] comparatively, the length of the left main bronchus is compared to the length of the right main bronchus and found to be larger.…”
Section: Lengths Of Right and Left Main Bronchusmentioning
confidence: 99%
See 1 more Smart Citation
“…In studies conducted on adults, the lengths of the main bronchus were found to be greater in males than in females [7,18,20,24,27,36]. In studies examining the lengths of the right and left main bronchus in children [18,25] and adults [18,20,21,24,27,37] comparatively, the length of the left main bronchus is compared to the length of the right main bronchus and found to be larger.…”
Section: Lengths Of Right and Left Main Bronchusmentioning
confidence: 99%
“…The diameters of the right and left main bronchus were found to be larger in men than in women in all of the studies (Tables V and VI.). All studies measuring the transverse diameters of the right and left main bronchus in children [2,6,18,23,25,33,35] and adults [15,18,20,21,24,27,37,42] found that the right main bronchus was larger than the left main bronchus. The value of the main bronchus' transverse diameter was found to be greater than the transverse diameter of the left main bronchus.…”
Section: Transverse Diamaters Of Right and Left Maın Bronchusmentioning
confidence: 99%
“…The trachea model used in this study was designed based on anatomical dimensions obtained from morphometric studies of Korean cadavers (16,17) and computed tomography scans from New Zealand subjects. (18) The average dimensions of male subjects were used with a trachea length of 104 mm and anteroposterior diameter of 23 mm and a transverse diameter of 19 mm, as given in Figure 3.…”
Section: Design Of Trachea Prototypementioning
confidence: 99%